Porous silicon nitride ceramic material and preparation method thereof

By adding metal oxides and rare earth metal oxides in the preparation process of porous silicon nitride ceramics, and using PMMA microspheres as pore-making agents, combined with ultra-high temperature rapid sintering technology, the closed porosity and mechanical properties of the ceramics were successfully improved, and the problem of insufficient ceramic strength in the existing technology was solved.

CN119797956APending Publication Date: 2025-04-11XI AN JIAOTONG UNIV

Patent Information

Application Number
CN202510036043.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively prepare porous silicon nitride ceramics with high closed porosity, resulting in insufficient strength and difficult to meet the performance requirements of different application scenarios.

Method used

Porous silicon nitride ceramic powder, metal oxide powder and rare earth metal oxide powder are mixed to form a ceramic matrix, and pore-forming agent such as PMMA microspheres are added thereto. Porous silicon nitride ceramics are prepared through ball milling, drying, grinding, dry press forming, glue removal treatment and ultra-high temperature rapid sintering.

Benefits of technology

The high closed porosity of porous silicon nitride ceramics is achieved, which improves its mechanical properties, and can adjust the porosity and bending strength to meet the needs of different application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797956A_ABST
    Figure CN119797956A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of porous silicon nitride ceramics, and discloses a porous silicon nitride ceramic material and a preparation method thereof. The preparation method comprises the following steps: mixing silicon nitride ceramic powder, metal oxide powder and rare earth metal oxide powder, adding a pore forming agent and a grinding medium, mixing, and carrying out ball milling, drying, grinding and sieving to obtain ceramic powder; carrying out dry pressing molding on the ceramic powder to obtain a ceramic green body; carrying out glue discharging treatment on the ceramic green body to obtain a precursor; the precursor is subjected to ultrahigh-temperature rapid sintering treatment, and the porous silicon nitride ceramic is obtained; wherein the sintering temperature ranges from 1600 DEG C to 1900 DEG C. According to the porous silicon nitride ceramic prepared by the method, the porosity is wide and adjustable in range, and the porous silicon nitride ceramic with closed spherical pore morphology can be prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of silicon nitride ceramics, and in particular to a porous silicon nitride ceramic material and a preparation method thereof. Background Art

[0002] Silicon nitride ceramic materials have the advantages of high strength, low density, high toughness, high thermal shock resistance, corrosion resistance and high temperature resistance. They are widely used in metallurgy, machinery, aerospace, chemical industry, electronics, biomedicine and other fields.

[0003] The performance requirements of porous silicon nitride ceramics change with the change of application scenarios, and the performance of silicon nitride ceramics is closely related to its porosity, phase change rate and micromorphology. Through research, technicians in this field have pointed out that the strength of closed pore structures such as spherical pores is greater than that of open pore structures. A large number of studies have attempted to prepare porous silicon nitride ceramics by methods such as pressureless sintering, gas pressure sintering, self-propagating sintering and microwave sintering. The obtained porous silicon nitride ceramics are all high-β-phase porous silicon nitride ceramics, and a large number of interconnected open pores are formed between the overlapping β-phase grains; in order to obtain closed pore porous ceramics with higher strength, the prior art proposes to prepare closed pore porous ceramics by combining spherical pore formers, but due to the long-term sintering of traditional methods, columnar grains grow, which destroys the spherical morphology of the pores, and it is difficult to obtain porous silicon nitride ceramics with a closed pore structure. Summary of the invention

[0004] In order to solve the above technical problems and promote the further application of porous silicon nitride ceramics, it is necessary to provide a preparation method of porous silicon nitride ceramics that can increase the proportion of closed pores in ceramics. Therefore, the present invention provides a porous silicon nitride ceramic material and a preparation method thereof.

[0005] A porous silicon nitride ceramic material and a preparation method thereof of the present invention are realized by the following technical scheme:

[0006] The first object of the present invention is to provide a method for preparing a porous silicon nitride ceramic, characterized in that it comprises the following steps:

[0007] Step 1, preparation of ceramic matrix:

[0008] Silicon nitride ceramic powder, metal oxide powder and rare earth metal oxide powder are mixed to obtain a ceramic matrix.

[0009] It should be noted that the present invention uses metal oxide powder and rare earth metal oxide together as liquid phase sintering aids, and introduces a large amount of liquid phase sintering aids into silicon nitride ceramic powder to promote and control the sintering and phase change process of silicon nitride ceramics.

[0010] In some preferred embodiments of the present invention, the metal oxide powder used is one or more of magnesium oxide, aluminum oxide, and silicon dioxide to ensure that the metal oxide powder used can achieve the above technical effects. In some more preferred embodiments of the present invention, the particle size of the metal oxide powder is 50nm to 500nm.

[0011] In some preferred embodiments of the present invention, the rare earth metal oxide powder is one or more of ytterbium oxide, yttrium oxide and lanthanum oxide, so as to ensure that the rare earth metal oxide powder used can achieve the above technical effects. In some more preferred embodiments of the present invention, the particle size of the rare earth metal oxide powder is 50nm to 500nm.

[0012] In some more preferred embodiments of the present invention, the silicon nitride ceramic powder accounts for 80wt% to 90wt% of the total mass of the ceramic matrix; the metal oxide powder accounts for 4wt% to 8wt% of the total mass of the ceramic matrix; and the rare earth metal oxide powder accounts for 6wt% to 12wt% of the total mass of the ceramic matrix, so that the silicon nitride ceramic powder, the metal oxide powder and the rare earth metal oxide powder are within the above-mentioned dosage range, thereby achieving the pore morphology control and phase change of the porous silicon nitride ceramic through the above-mentioned dosage ratio.

[0013] Step 2, preparation of ceramic slurry:

[0014] After adding pore formers and grinding media into the ceramic matrix and mixing, ceramic slurry is obtained.

[0015] It should be noted that the present invention achieves the purpose of increasing the porosity of ceramics by adding a pore-forming agent. Among them, in some preferred embodiments of the present invention, the pore-forming agent is polymethyl methacrylate microspheres, and the particle size of the polymethyl methacrylate microspheres is 3μm to 10μm. The present invention uses polymethyl methacrylate microspheres as high sphericity templates, adds high sphericity templates when preparing ceramic slurry, and then removes them through subsequent debinding treatment, thereby retaining closed spherical pores in porous silicon nitride ceramics, so that the porous silicon nitride ceramics finally prepared have high closed porosity. And for the convenience of description, the present invention will use PMMA microspheres to represent polymethyl methacrylate microspheres.

[0016] In some preferred embodiments of the present invention, the added amount of the pore former is 5.3wt% to 17.6wt% of the total mass of the ceramic matrix, so as to ensure that the pore former added in the present invention can improve the closed porosity of the porous silicon nitride ceramic.

[0017] In some preferred embodiments of the present invention, the grinding medium is anhydrous ethanol, and the mass ratio of the grinding medium to the ceramic matrix is ​​1:5-10.

[0018] Step 3, preparation of ceramic powder:

[0019] The ceramic slurry is subjected to ball milling treatment, and then dried, ground and sieved in sequence to obtain ceramic powder.

[0020] It should be noted that, in some preferred embodiments of the present invention, the ball-to-material ratio of the ball milling treatment is 1:2-5, the ball milling speed is 300 rpm-600 rpm, and the ball milling time is 4 h-12 h.

[0021] In some preferred embodiments of the present invention, the drying temperature is 80° C. to 120° C., and the drying time is 8 h to 16 h.

[0022] In some preferred embodiments of the present invention, the grinding is performed until the particle size of the ceramic powder can pass through a 80-120 mesh sieve.

[0023] Step 4, preparation of ceramic body:

[0024] The ceramic powder is dry-pressed to obtain a ceramic green body.

[0025] It should be noted that, in some preferred embodiments of the present invention, the pressure of the dry pressing is 1 MPa to 5 MPa, and the pressing time is 50 s to 120 s.

[0026] In some preferred embodiments of the present invention, the ceramic powder is placed in a 10 mm circular mold or a 10 mm×30 mm rectangular mold for dry pressing.

[0027] Step 5, preparation of precursor:

[0028] The ceramic body is subjected to a debinding treatment to remove the pore-forming agent in the ceramic body to obtain a precursor.

[0029] It should be noted that in some preferred embodiments of the present invention, during the debinding treatment, the heating rate is 0.5°C / min to 2°C / min, the treatment temperature is 500°C to 600°C, and the insulation time is 4h to 6h, so as to ensure that the pore-forming agent in the ceramic green body can decompose and volatilize under the high temperature of the debinding treatment, and then remove the pore-forming agent in the ceramic green body to increase the closed porosity in the precursor material. The increase in closed porosity is beneficial to alleviating stress concentration during ceramic bearing and improving the mechanical properties of the final ceramic material.

[0030] In some more preferred embodiments of the present invention, the heating rate of the debinding treatment is 1°C / min.

[0031] In some more preferred embodiments of the present invention, the heat preservation time of the debinding treatment is 5 hours.

[0032] In some more preferred embodiments of the present invention, after the heat preservation of the debinding treatment is completed, the temperature is lowered to room temperature at a rate of 10°C / min.

[0033] Step 6: Ultra-high temperature rapid sintering treatment:

[0034] The ultra-high temperature rapid sintering temperature is controlled by controlling the output power of the power supply to obtain the porous silicon nitride ceramic.

[0035] It should be noted that the present invention further performs ultra-high temperature rapid sintering treatment on the precursor with high closed porosity obtained above, so that the component particles in the precursor can be more firmly bonded in a short time, the open pores in the ceramic can be closed and the closed porosity can be increased. The porosity of the porous silicon nitride ceramic finally obtained is 14.7% to 31.4%; and the phase change rate of α-phase silicon nitride to β-phase silicon nitride in the ceramic material can be controlled at 26.1% to 69.6%.

[0036] In the present invention, the sintering temperature is 1600°C to 1900°C.

[0037] In some more preferred embodiments of the present invention, the holding time of the ultra-high temperature rapid sintering process is 2 minutes to 4 minutes.

[0038] The second object of the present invention is to provide a porous silicon nitride ceramic prepared by the above preparation method.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] The present invention uses metal oxide powder and rare earth metal oxide as liquid phase sintering aids, and obtains a ceramic matrix by mixing silicon nitride ceramic powder, metal oxide powder and rare earth metal oxide powder, so as to introduce a large amount of liquid phase sintering aids into the silicon nitride ceramic powder, thereby promoting and controlling the closure of open pores and phase change process of silicon nitride ceramics. Then, a pore-forming agent is added to the ceramic matrix to form a ceramic slurry, and then the ceramic slurry is ball-milled, dried, ground and sieved to obtain a ceramic powder. The ceramic powder is dry-pressed to obtain a ceramic body. Then, the ceramic body is subjected to a binder removal treatment so that the pore-forming agent in the ceramic body can be decomposed and volatilized at a high temperature during the binder removal treatment, thereby removing the pore-forming agent in the ceramic body to increase the closed porosity in the precursor material; finally, the precursor with high closed porosity is further subjected to an ultra-high temperature rapid sintering treatment to achieve a stronger bond between the component particles in the precursor in a short time, thereby achieving closure of the open pores in the ceramic, and finally obtaining a porous silicon nitride ceramic with a porosity of 14.7% to 31.4%; and the phase change rate of α-phase silicon nitride to β-phase silicon nitride in the ceramic material can be controlled within a range of 26.1% to 69.6%, thereby achieving regulation of the ceramic phase change rate while increasing the closed porosity of the ceramic material, thereby promoting further application of porous silicon nitride ceramics.

[0041] The present invention has high sintering efficiency and can realize ceramic sintering and phase change in a short time of 0.5min to 10min, thereby greatly improving the efficiency of ceramic preparation and reducing the ceramic production cost.

[0042] The porous ceramic pores in the porous silicon nitride ceramics prepared by the present invention are closed spherical pores, which are beneficial to alleviate stress concentration when the ceramic is loaded and improve the mechanical properties of the silicon nitride ceramics; and the present invention can effectively control the porosity of the ceramic within the range of 14.7% to 31.4% by changing the addition amount of the pore-forming agent, and can also control the bending strength of the ceramic within the range of 96.83MPa to 380.53MPa; and the present invention can control the phase change rate and pore morphology of the porous silicon nitride ceramics by adjusting the sintering temperature and the holding time of the sintering treatment to meet the needs of different application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1The figures are electron scanning electron microscope images of the cross-sections of the porous silicon nitride ceramics of Example 1, Example 2 and Example 3, wherein (a) is an electron scanning electron microscope image of the cross-section of the porous silicon nitride ceramic of Example 1 at a scale of 50 μm, (b) is an electron scanning electron microscope image of the cross-section of the porous silicon nitride ceramic of Example 2 at a scale of 50 μm, (c) is an electron scanning electron microscope image of the cross-section of the porous silicon nitride ceramic of Example 3 at a scale of 50 μm, (d) is an electron scanning electron microscope image of the cross-section of the porous silicon nitride ceramic of Example 1 at a scale of 10 μm, (e) is an electron scanning electron microscope image of the cross-section of the porous silicon nitride ceramic of Example 2 at a scale of 10 μm, and (f) is an electron scanning electron microscope image of the cross-section of the porous silicon nitride ceramic of Example 3 at a scale of 10 μm.

[0044] Figure 2 The electron scanning electron microscope images of the cross-section of the porous silicon nitride ceramic of Example 1, Example 4, Example 5 and Comparative Example 1, wherein (a) is an electron scanning electron microscope image of the cross-section of the porous silicon nitride ceramic of Example 4 at a scale of 10 μm, (b) is an electron scanning electron microscope image of the cross-section of the porous silicon nitride ceramic of Example 1 at a scale of 10 μm, (c) is an electron scanning electron microscope image of the cross-section of the porous silicon nitride ceramic of Example 5 at a scale of 10 μm, and (d) is an electron scanning electron microscope image of the cross-section of the porous silicon nitride ceramic of Comparative Example 1. (e) is a scanning electron microscope image of the cross-section of the porous silicon nitride ceramic at a scale of 10 μm, (f) is a scanning electron microscope image of the cross-section of the porous silicon nitride ceramic at a scale of 1 μm, (g) is a scanning electron microscope image of the cross-section of the porous silicon nitride ceramic at a scale of 1 μm, and (h) is a scanning electron microscope image of the cross-section of the porous silicon nitride ceramic of Comparative Example 1 at a scale of 2 μm.

[0045] Figure 3 1 and 2 are XRD diagrams of the porous silicon nitride ceramics of Example 1, Example 6 and Example 7.

[0046] Figure 4 It is a dotted line graph of the flexural strength and porosity of the porous silicon nitride ceramics of Example 1, Example 2 and Example 3. DETAILED DESCRIPTION

[0047] The technical solutions in the embodiments of the present invention will be described clearly and completely below. It should be noted that in the following embodiments of the present invention, the carbon felt used in the ultra-high temperature rapid sintering process has a size of 3mm×20mm×120mm; and the sintering atmosphere is an inert gas environment (argon or nitrogen).

[0048] Example 1

[0049] This embodiment provides a porous silicon nitride ceramic, which is prepared by the following steps:

[0050] Step 1, preparation of ceramic matrix:

[0051] Silicon nitride ceramic powder, aluminum oxide powder and yttrium oxide powder were mixed in a mass ratio of 80:8:12 to obtain a ceramic matrix.

[0052] Step 2, preparation of ceramic slurry:

[0053] Take 10 g of the ceramic matrix obtained in step 1 above, add 1.11 g of PMMA microspheres with a diameter of 5 μm, and 100 g of anhydrous ethanol to mix to obtain a ceramic slurry.

[0054] Step 3, preparation of ceramic powder:

[0055] 3.1) The ceramic slurry was ball-milled using silicon nitride ball milling beads with a ball-to-material ratio of 1:2. The slurry was ball-milled at a rotation speed of 300 rpm for 12 h to obtain a ball-milled slurry.

[0056] 3.2) The ball-milled slurry obtained in 3.1) above was placed in a drying oven at 80° C. for 12 h to obtain a ceramic block.

[0057] 3.3) The ceramic block obtained in 3.2) above is placed in a grinding mortar for grinding, and then passed through a 100-mesh sieve to obtain ceramic powder.

[0058] Step 4, preparation of ceramic body:

[0059] The ceramic powder obtained in 3.3) above was placed in a 10 mm circular mold and pressed at 2 MPa for 90 s to obtain a ceramic green body.

[0060] Step 5, preparation of precursor:

[0061] The ceramic body obtained in the above step 4 was placed in a muffle furnace and kept at 600° C. for 6 hours to remove the PMMA microspheres. After cooling to room temperature, a precursor was obtained.

[0062] Step 6: Ultra-high temperature rapid sintering treatment:

[0063] The precursor obtained in the above step 5 is subjected to ultra-high temperature rapid sintering, and a constant sintering temperature is ensured by controlling the power output of the power supply to 1300 W, and the heat preservation time is 3 minutes to obtain porous silicon nitride ceramics.

[0064] Example 2

[0065] This embodiment provides a porous silicon nitride ceramic, which is prepared by the following steps:

[0066] Step 1, preparation of ceramic matrix:

[0067] Silicon nitride ceramic powder, aluminum oxide powder and yttrium oxide powder were mixed in a mass ratio of 80:8:12 to obtain a ceramic matrix.

[0068] Step 2, preparation of ceramic slurry:

[0069] Take 10 g of the ceramic matrix obtained in step 1 above, add 0.53 g of PMMA microspheres with a diameter of 5 μm, and 100 g of anhydrous ethanol to mix to obtain a ceramic slurry.

[0070] Step 3, preparation of ceramic powder:

[0071] 3.1) The ceramic slurry was ball-milled using silicon nitride ball milling beads with a ball-to-material ratio of 1:2. The slurry was ball-milled at a rotation speed of 300 rpm for 12 h to obtain a ball-milled slurry.

[0072] 3.2) The ball-milled slurry obtained in 3.1) above was placed in a drying oven at 80° C. for 12 h to obtain a ceramic block.

[0073] 3.3) The ceramic block obtained in 3.2) above is placed in a grinding mortar for grinding, and then passed through a 100-mesh sieve to obtain ceramic powder.

[0074] Step 4, preparation of ceramic body:

[0075] The ceramic powder obtained in 3.3) above was placed in a 10 mm circular mold and pressed at 2 MPa for 90 s to obtain a ceramic green body.

[0076] Step 5, preparation of precursor:

[0077] The ceramic body obtained in the above step 4 was placed in a muffle furnace and kept at 600° C. for 6 hours to remove the PMMA microspheres. After cooling to room temperature, a precursor was obtained.

[0078] Step 6: Ultra-high temperature rapid sintering treatment:

[0079] The precursor obtained in the above step 5 is subjected to ultra-high temperature rapid sintering, and a constant sintering temperature is ensured by controlling the power output of the power supply to 1300 W, and the heat preservation time is 3 minutes to obtain porous silicon nitride ceramics.

[0080] That is, the difference between this embodiment and embodiment 1 is only that:

[0081] In step 2 of this embodiment, the added amount of PMMA microspheres with a diameter of 5 μm is 0.53 g.

[0082] Example 3

[0083] This embodiment provides a porous silicon nitride ceramic, which is prepared by the following steps:

[0084] Step 1, preparation of ceramic matrix:

[0085] Silicon nitride ceramic powder, aluminum oxide powder and yttrium oxide powder were mixed in a mass ratio of 80:8:12 to obtain a ceramic matrix.

[0086] Step 2, preparation of ceramic slurry:

[0087] Take 10 g of the ceramic matrix obtained in step 1 above, add 1.76 g of PMMA microspheres with a diameter of 5 μm, and 100 g of anhydrous ethanol to mix to obtain a ceramic slurry.

[0088] Step 3, preparation of ceramic powder:

[0089] 3.1) The ceramic slurry was ball-milled using silicon nitride ball milling beads with a ball-to-material ratio of 1:2. The slurry was ball-milled at a rotation speed of 300 rpm for 12 h to obtain a ball-milled slurry.

[0090] 3.2) The ball-milled slurry obtained in 3.1) above was placed in a drying oven at 80° C. for 12 h to obtain a ceramic block.

[0091] 3.3) The ceramic block obtained in 3.2) above is placed in a grinding mortar for grinding, and then passed through a 100-mesh sieve to obtain ceramic powder.

[0092] Step 4, preparation of ceramic body:

[0093] The ceramic powder obtained in 3.3) above was placed in a 10 mm circular mold and pressed at 2 MPa for 90 s to obtain a ceramic green body.

[0094] Step 5, preparation of precursor:

[0095] The ceramic body obtained in the above step 4 was placed in a muffle furnace and kept at 600° C. for 6 hours to remove the PMMA microspheres. After cooling to room temperature, a precursor was obtained.

[0096] Step 6: Ultra-high temperature rapid sintering treatment:

[0097] The precursor obtained in the above step 5 is subjected to ultra-high temperature rapid sintering, and a constant sintering temperature is ensured by controlling the power output of the power supply to 1300 W, and the heat preservation time is 3 minutes to obtain porous silicon nitride ceramics.

[0098] That is, the difference between this embodiment and embodiment 1 is only that:

[0099] In step 2 of this embodiment, the added amount of PMMA microspheres with a diameter of 5 μm is 1.76 g.

[0100] Example 4

[0101] This embodiment provides a porous silicon nitride ceramic, which is prepared by the following steps:

[0102] Step 1, preparation of ceramic matrix:

[0103] Silicon nitride ceramic powder, aluminum oxide powder and yttrium oxide powder were mixed in a mass ratio of 80:8:12 to obtain a ceramic matrix.

[0104] Step 2, preparation of ceramic slurry:

[0105] Take 10 g of the ceramic matrix obtained in step 1 above, add 1.11 g of PMMA microspheres with a diameter of 5 μm, and 100 g of anhydrous ethanol to mix to obtain a ceramic slurry.

[0106] Step 3, preparation of ceramic powder:

[0107] 3.1) The ceramic slurry was ball-milled using silicon nitride ball milling beads with a ball-to-material ratio of 1:2. The slurry was ball-milled at a rotation speed of 300 rpm for 12 h to obtain a ball-milled slurry.

[0108] 3.2) The ball-milled slurry obtained in 3.1) above was placed in a drying oven at 80° C. for 12 h to obtain a ceramic block.

[0109] 3.3) The ceramic block obtained in 3.2) above is placed in a grinding mortar for grinding, and then passed through a 100-mesh sieve to obtain ceramic powder.

[0110] Step 4, preparation of ceramic body:

[0111] The ceramic powder obtained in 3.3) above was placed in a 10 mm circular mold and pressed at 2 MPa for 90 s to obtain a ceramic green body.

[0112] Step 5, preparation of precursor:

[0113] The ceramic body obtained in the above step 4 was placed in a muffle furnace and kept at 600° C. for 6 hours to remove the PMMA microspheres. After cooling to room temperature, a precursor was obtained.

[0114] Step 6: Ultra-high temperature rapid sintering treatment:

[0115] The precursor obtained in the above step 5 is subjected to ultra-high temperature rapid sintering, and a constant sintering temperature is ensured by controlling the power output of the power supply to 1300 W, and the heat preservation time is 2 minutes to obtain porous silicon nitride ceramics.

[0116] That is, the difference between this embodiment and embodiment 1 is only that:

[0117] In step 6 of this embodiment, the holding time during the ultra-high temperature rapid sintering process is 2 minutes.

[0118] Example 5

[0119] This embodiment provides a porous silicon nitride ceramic, which is prepared by the following steps:

[0120] Step 1, preparation of ceramic matrix:

[0121] Silicon nitride ceramic powder, aluminum oxide powder and yttrium oxide powder were mixed in a mass ratio of 80:8:12 to obtain a ceramic matrix.

[0122] Step 2, preparation of ceramic slurry:

[0123] Take 10 g of the ceramic matrix obtained in step 1 above, add 1.11 g of PMMA microspheres with a diameter of 5 μm, and 100 g of anhydrous ethanol to mix to obtain a ceramic slurry.

[0124] Step 3, preparation of ceramic powder:

[0125] 3.1) The ceramic slurry was ball-milled using silicon nitride ball milling beads with a ball-to-material ratio of 1:2. The slurry was ball-milled at a rotation speed of 300 rpm for 12 h to obtain a ball-milled slurry.

[0126] 3.2) The ball-milled slurry obtained in 3.1) above was placed in a drying oven at 80° C. for 12 h to obtain a ceramic block.

[0127] 3.3) The ceramic block obtained in 3.2) above is placed in a grinding mortar for grinding, and then passed through a 100-mesh sieve to obtain ceramic powder.

[0128] Step 4, preparation of ceramic body:

[0129] The ceramic powder obtained in 3.3) above was placed in a 10 mm circular mold and pressed at 2 MPa for 90 s to obtain a ceramic green body.

[0130] Step 5, preparation of precursor:

[0131] The ceramic body obtained in the above step 4 was placed in a muffle furnace and kept at 600° C. for 6 hours to remove the PMMA microspheres. After cooling to room temperature, a precursor was obtained.

[0132] Step 6: Ultra-high temperature rapid sintering treatment:

[0133] The precursor obtained in the above step 5 is subjected to ultra-high temperature rapid sintering, and a constant sintering temperature is ensured by controlling the power output of the power supply to 1300 W, and the heat preservation time is 4 minutes to obtain porous silicon nitride ceramics.

[0134] That is, the difference between this embodiment and embodiment 1 is only that:

[0135] In step 6 of this embodiment, the holding time during the ultra-high temperature rapid sintering process is 4 minutes.

[0136] Example 6

[0137] This embodiment provides a porous silicon nitride ceramic, which is prepared by the following steps:

[0138] Step 1, preparation of ceramic matrix:

[0139] Silicon nitride ceramic powder, aluminum oxide powder and yttrium oxide powder were mixed in a mass ratio of 80:8:12 to obtain a ceramic matrix.

[0140] Step 2, preparation of ceramic slurry:

[0141] Take 10 g of the ceramic matrix obtained in step 1 above, add 0.53 g of PMMA microspheres with a diameter of 5 μm, and 100 g of anhydrous ethanol to mix to obtain a ceramic slurry.

[0142] Step 3, preparation of ceramic powder:

[0143] 3.1) The ceramic slurry was ball-milled using silicon nitride ball milling beads with a ball-to-material ratio of 1:2. The slurry was ball-milled at a rotation speed of 300 rpm for 12 h to obtain a ball-milled slurry.

[0144] 3.2) The ball-milled slurry obtained in 3.1) above was placed in a drying oven at 80° C. for 12 h to obtain a ceramic block.

[0145] 3.3) The ceramic block obtained in 3.2) above is placed in a grinding mortar for grinding, and then passed through a 100-mesh sieve to obtain ceramic powder.

[0146] Step 4, preparation of ceramic body:

[0147] The ceramic powder obtained in 3.3) above was placed in a 10 mm circular mold and pressed at 2 MPa for 90 s to obtain a ceramic green body.

[0148] Step 5, preparation of precursor:

[0149] The ceramic body obtained in the above step 4 was placed in a muffle furnace and kept at 600° C. for 6 hours to remove the PMMA microspheres. After cooling to room temperature, a precursor was obtained.

[0150] Step 6: Ultra-high temperature rapid sintering treatment:

[0151] The precursor obtained in the above step 5 is subjected to ultra-high temperature rapid sintering, and a constant sintering temperature is ensured by controlling the power output of the power supply to 1200 W, and the heat preservation time is 3 minutes to obtain porous silicon nitride ceramics.

[0152] That is, the difference between this embodiment and embodiment 2 is only that:

[0153] In step 6 of this embodiment, the output power of the DC power supply is 1200W.

[0154] Example 7

[0155] This embodiment provides a porous silicon nitride ceramic, which is prepared by the following steps:

[0156] Step 1, preparation of ceramic matrix:

[0157] Silicon nitride ceramic powder, aluminum oxide powder and yttrium oxide powder were mixed in a mass ratio of 80:8:12 to obtain a ceramic matrix.

[0158] Step 2, preparation of ceramic slurry:

[0159] Take 10 g of the ceramic matrix obtained in step 1 above, add 1.76 g of PMMA microspheres with a diameter of 5 μm, and 100 g of anhydrous ethanol to mix to obtain a ceramic slurry.

[0160] Step 3, preparation of ceramic powder:

[0161] 3.1) The ceramic slurry was ball-milled using silicon nitride ball milling beads with a ball-to-material ratio of 1:2. The slurry was ball-milled at a rotation speed of 300 rpm for 12 h to obtain a ball-milled slurry.

[0162] 3.2) The ball-milled slurry obtained in 3.1) above was placed in a drying oven at 80° C. for 12 h to obtain a ceramic block.

[0163] 3.3) The ceramic block obtained in 3.2) above is placed in a grinding mortar for grinding, and then passed through a 100-mesh sieve to obtain ceramic powder.

[0164] Step 4, preparation of ceramic body:

[0165] The ceramic powder obtained in 3.3) above was placed in a 10 mm circular mold and pressed at 2 MPa for 90 s to obtain a ceramic green body.

[0166] Step 5, preparation of precursor:

[0167] The ceramic body obtained in the above step 4 was placed in a muffle furnace and kept at 600° C. for 6 hours to remove the PMMA microspheres. After cooling to room temperature, a precursor was obtained.

[0168] Step 6: Ultra-high temperature rapid sintering treatment:

[0169] The precursor obtained in the above step 5 is subjected to ultra-high temperature rapid sintering, and a constant sintering temperature is ensured by controlling the power output of the power supply to 1400 W, and the heat preservation time is 3 minutes to obtain porous silicon nitride ceramics.

[0170] That is, the difference between this embodiment and embodiment 3 is only that:

[0171] In step 2 of this embodiment, the output power of the DC power supply is 1400W.

[0172] Comparative Example 1

[0173] This embodiment provides a porous silicon nitride ceramic, which is prepared by the following steps:

[0174] Step 1, preparation of ceramic matrix:

[0175] Silicon nitride ceramic powder, aluminum oxide powder and yttrium oxide powder were mixed in a mass ratio of 90:4:6 to obtain a ceramic matrix.

[0176] Step 2, preparation of ceramic slurry:

[0177] 10 g of the ceramic matrix obtained in step 1 above was mixed with 100 g of anhydrous ethanol to obtain a ceramic slurry.

[0178] Step 3, preparation of ceramic powder:

[0179] 3.1) The ceramic slurry was ball-milled using silicon nitride ball milling beads with a ball-to-material ratio of 1:2. The slurry was ball-milled at a rotation speed of 300 rpm for 12 h to obtain a ball-milled slurry.

[0180] 3.2) The ball-milled slurry obtained in 3.1) above was placed in a drying oven at 80° C. for 12 h to obtain a ceramic block.

[0181] 3.3) The ceramic block obtained in 3.2) above is placed in a grinding mortar for grinding, and then passed through a 100-mesh sieve to obtain ceramic powder.

[0182] Step 4, preparation of ceramic body:

[0183] The ceramic powder obtained in 3.3) above was placed in a 10 mm circular mold and pressed at 2 MPa for 90 s to obtain a ceramic green body.

[0184] Step 5: Ultra-high temperature rapid sintering treatment:

[0185] The precursor obtained in the above step 5 is subjected to ultra-high temperature rapid sintering, and a constant sintering temperature is ensured by controlling the power output of the power supply to 1300 W, and the heat preservation time is 3 minutes to obtain porous silicon nitride ceramics.

[0186] This comparative example provides a porous silicon nitride ceramic, and the difference between this comparative example and Example 1 is only that:

[0187] In this comparative example, PMMA microspheres are not added, so the debinding step is omitted; and in this comparative example, the mass ratio of silicon nitride ceramic powder, aluminum oxide powder and yttrium oxide powder is 90:4:6, that is, the amount of liquid phase sintering aid added in this comparative example is reduced relative to that in Example 1.

[0188] Experimental Section

[0189] (I) Porosity test of closed pores

[0190] The present invention tests the porosity of the porous silicon nitride ceramics prepared in Examples 1 to 7. The test method is: the ceramic volume density is measured by the Archimedean drainage method, and the porosity of the closed pores is calculated. The test results are shown in Table 1.

[0191] Table 1 Porosity test results of closed pores

[0192] Porosity of closed pores Example 1 20.9% Example 2 14.7% Example 3 31.4% Example 4 24.7% Example 5 18.4% Example 6 22.9% Example 7 21.7%

[0193] It can be seen from the test results in Table 1 that using PMMA microspheres as pore-forming agents can effectively improve the porosity of ceramics, and the porosity can be adjusted in a wide range.

[0194] (II) Bending strength test of ceramics

[0195] The present invention tests the flexural strength of the porous silicon nitride ceramics prepared in Examples 1 to 5. The flexural strength test method adopts the three-point bending test method, and the test conditions are: the sample size is 1.5 mm × 2 mm × 24 mm, the span is 20 mm, and the loading rate is 0.2 mm / min. The test results are shown in Table 2.

[0196] Table 2 Flexural strength test results of ceramics

[0197] Example 1 Example 2 Example 3 Example 4 Example 5 Bending strength 298.68MPa 380.53MPa 96.83MPa 169.64MPa 275.82MPa

[0198] It can be seen from the test results in Table 2 that the porous silicon nitride ceramics obtained by this method have strong bending strength.

[0199] (III) Morphology test

[0200] In order to explore the effect of different addition amounts of PMMA microspheres on the SEM cross-sectional morphology of porous silicon nitride ceramics, the present invention takes Example 1, Example 2 and Example 3 as examples, and performs electron scanning electron microscopy tests on the cross-sectional morphology of porous silicon nitride ceramics, and the test results are as follows: Figure 1 shown.

[0201] Figure 1 The figures are electron scanning electron microscope images of the cross-sections of the porous silicon nitride ceramics of Example 1, Example 2 and Example 3, wherein (a) is an electron scanning electron microscope image of the cross-section of the porous silicon nitride ceramic of Example 1 at a scale of 50 μm, (b) is an electron scanning electron microscope image of the cross-section of the porous silicon nitride ceramic of Example 2 at a scale of 50 μm, (c) is an electron scanning electron microscope image of the cross-section of the porous silicon nitride ceramic of Example 3 at a scale of 50 μm, (d) is an electron scanning electron microscope image of the cross-section of the porous silicon nitride ceramic of Example 1 at a scale of 10 μm, (e) is an electron scanning electron microscope image of the cross-section of the porous silicon nitride ceramic of Example 2 at a scale of 10 μm, and (f) is an electron scanning electron microscope image of the cross-section of the porous silicon nitride ceramic of Example 3 at a scale of 10 μm.

[0202] Depend on Figure 1 It can be seen that the porous silicon nitride ceramic sections of Examples 1 to 3 all have a high closed porosity, uniform pore distribution and uniform pore size, which indicates that the PMMA microspheres added in the present invention have good dispersibility in the ceramic slurry, so that the dispersed spherical pores can be retained in the ceramic, thereby effectively improving the closed porosity of the ceramic material. And by comparing the pore distribution of Examples 1, 2 and 3, it can be seen that as the amount of PMMA microspheres added increases, the closed pores of the ceramic also increase, which indicates that within the range of PMMA microsphere addition defined in the present invention, the porosity of the ceramic can be regulated by changing the amount of PMMA microspheres added according to the actual porosity requirements.

[0203] Figure 2 The electron scanning electron microscope images of the cross-section of the porous silicon nitride ceramic of Example 1, Example 4, Example 5 and Comparative Example 1, wherein (a) is an electron scanning electron microscope image of the cross-section of the porous silicon nitride ceramic of Example 4 at a scale of 10 μm, (b) is an electron scanning electron microscope image of the cross-section of the porous silicon nitride ceramic of Example 1 at a scale of 10 μm, (c) is an electron scanning electron microscope image of the cross-section of the porous silicon nitride ceramic of Example 5 at a scale of 10 μm, and (d) is an electron scanning electron microscope image of the cross-section of the porous silicon nitride ceramic of Comparative Example 1. (e) is a scanning electron microscope image of the cross-section of the porous silicon nitride ceramic at a scale of 10 μm, (f) is a scanning electron microscope image of the cross-section of the porous silicon nitride ceramic at a scale of 1 μm, (g) is a scanning electron microscope image of the cross-section of the porous silicon nitride ceramic at a scale of 1 μm, and (h) is a scanning electron microscope image of the cross-section of the porous silicon nitride ceramic of Comparative Example 1 at a scale of 2 μm.

[0204] Depend on Figure 2It can be seen that when the holding time is 2, 3, and 4 minutes respectively, the porous silicon nitride ceramics prepared in Examples 4, 1, and 5 can obtain closed spherical pores, and the pore morphology of the porous silicon nitride ceramics can be adjusted by changing the sintering time. However, the pore morphology of the porous ceramic in Comparative Example 1 is irregular, and it is impossible to ensure whether the pores are closed. It proves that the ultra-high temperature rapid sintering method combined with PMMA microsphere pore formation has a regulating effect on the pore morphology of porous silicon nitride ceramics.

[0205] (IV) Phase change rate test of ceramics

[0206] In order to explore the influence of different sintering temperatures on the phase change rate of porous silicon nitride ceramics, the present invention conducted XRD tests on the porous silicon nitride ceramics prepared in Example 1, Example 6, and Example 7. The test results are as follows: Figure 3 And as shown in Table 3. Among them, Figure 3 The XRD patterns of porous silicon nitride ceramics prepared in Example 1, Example 6 and Example 7 are shown in Table 3. Figure 3 The corresponding phase change rate is obtained from the test results.

[0207] Table 3 Phase transformation rate of porous silicon nitride ceramics

[0208] Example 1 Example 6 Example 7 Phase change rate of ceramics 51.5% 26.1% 69.6%

[0209] Depend on Figure 3 It can be seen that as the output power increases, the sintering temperature during the sintering process increases, thereby greatly improving the phase change rate of the ceramic. This shows that the present invention can adjust the phase change rate of porous silicon nitride ceramics by adjusting the sintering temperature.

[0210] From the test results in Table 3, it can be seen that the phase change rate of ceramics sintered by this method is variable in a wide range, and the phase change process of ceramics can be changed by controlling the sintering temperature of the ceramics to obtain the desired phase change rate and micromorphology ceramics.

[0211] In order to further explore the effect of different addition amounts of PMMA microspheres on the flexural strength and porosity of ceramics, the present invention also arranges the flexural strength and porosity of Example 1, Example 2 and Example 3 as follows: Figure 4 shown.

[0212] Figure 4The dotted line graphs of the flexural strength and porosity of the porous silicon nitride ceramics of Example 1, Example 2 and Example 3 show that the flexural strength of the ceramic decreases with the increase of the amount of PMMA microspheres added, while the porosity of the ceramic increases with the increase of the amount of PMMA microspheres added. By changing the amount of PMMA microspheres added, the porosity of the ceramic can be effectively controlled within the range of 14.7% to 31.4%, and the flexural strength of the ceramic can be controlled within the range of 96.83MPa to 380.53MPa.

[0213] Obviously, the above embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A method for preparing porous silicon nitride ceramics, characterized in that: The following steps are involved: mixing silicon nitride ceramic powder, metal oxide powder and rare earth metal oxide powder to obtain a ceramic matrix; Adding a pore former and a grinding medium to the ceramic matrix and mixing them to obtain a ceramic slurry; After ball milling the ceramic slurry, it is dried, ground and sieved in sequence to obtain ceramic powder; dry-pressing the ceramic powder to obtain a ceramic body; Performing a binder removal treatment on the ceramic body to remove the pore-forming agent in the ceramic body to obtain a precursor; The porous silicon nitride ceramic is obtained by treating the precursor with ultra-high temperature rapid sintering; wherein the sintering temperature is 1600°C to 1900°C.

2. The preparation method according to claim 1, characterized in that The holding time of the ultra-high temperature rapid sintering process is 0.5 min to 10 min.

3. The preparation method according to claim 1, characterized in that: The silicon nitride ceramic powder is high-purity α-phase silicon nitride powder; The pore-forming agent is polymethyl methacrylate microspheres, and the particle size of the polymethyl methacrylate microspheres is 3 μm to 10 μm; The amount of the pore former added is 5.3wt% to 17.6wt% of the total mass of the ceramic matrix; The grinding medium is one or more of water, ethanol and isopropanol; The mass ratio of the grinding medium to the ceramic matrix is ​​1:5-10.

4. The preparation method according to claim 1, characterized in that: The metal oxide powder is one or more of magnesium oxide, aluminum oxide and silicon dioxide; The rare earth metal oxide powder is one or more of ytterbium oxide, yttrium oxide and lanthanum oxide.

5. The preparation method according to claim 1, characterized in that: The silicon nitride ceramic powder accounts for 80wt% to 90wt% of the total mass of the ceramic matrix; The metal oxide powder accounts for 4wt% to 8wt% of the total mass of the ceramic matrix; The rare earth metal oxide powder accounts for 6wt% to 12wt% of the total mass of the ceramic matrix.

6. The preparation method according to claim 1, characterized in that: The dry pressing pressure is 1 MPa to 5 MPa, and the pressing time is 50 s to 120 s.

7. The preparation method according to claim 1, characterized in that: During the debinding treatment, the heating rate is 0.5°C / min to 2°C / min, the treatment temperature is 500°C to 600°C, and the insulation time is 4h to 6h.

8. The preparation method according to claim 1, characterized in that: The ball-to-material ratio of the ball milling treatment is 1:2-5, the ball milling speed is 300rpm-600rpm, and the ball milling time is 4h-12h.

9. The preparation method according to claim 1, characterized in that: The particle size of the ceramic powder is 80-120 mesh.

10. A porous silicon nitride ceramic prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing porous silicon nitride ceramics

    CN101215183A

  • Preparation method of porous silicon nitride ceramic material with spherical pore structure

    CN104326766A

  • Method for preparing porous silicon nitride by spark plasma sintering

    CN105439620A

  • Preparation method of silicon nitride porous ceramic

    CN107056306A

  • Porous silicon nitride ceramic and preparation method thereof

    CN108585918A

Cited By

  • Large-aperture high-porosity porous silicon nitride ceramic material and preparation method thereof

    CN119977623A

  • A large-aperture and high-porosity porous silicon nitride ceramic material and its preparation method

    CN119977623B